National Legal Instrouments of Space Debris Problems - Бєглий, Олександр Васильович; Дабіжа, Марина Юріївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
The article deals with the national legal mechanisms for solving important problems of modern space - space debris, because of w hich further complicated by the development of space activities because of threats of disasters due to collisions with space debris objects.